PENGEMBANGAN TAMAN BACAAN MASYARAKAT SEBAGAI SUMBER BELAJAR - Sitepu, Bintang Petrus (JIV-Jurnal Ilmiah Visi, 2017)
Learning society is established and developed starting from reading community within this is in the mind, the role of Community Reading Centers (CRC) holds a strategic position in developing the community to become a reading and learning society. The Indonesian community and goverment made significant efforts to diseminate CRC through out Indonesia. This research was intended to describe the development of CRC particularly of those achieved financial assistance from the government. The research was conducted at 7 (seven) CRCs spread out in Banten Province in June through November 2011. Applying qualitative paradigm, the research collected data using observation, interview, and study document techniques. The data were analyzed qualitatively to draw conclusions and suggestions. The research findings show that the development of CRCs received the grant is not as expected. Based on the findings the research suggest the concerned institutions to intensify monitoring and supervision on the CRCs.